ANTI-NOCICEPTIVE EFFECT OF AGRIMONIA EUPATORIA EXTRACT ON A CISPLATIN-INDUCED NEUROPATHIC MODEL - Lee, Keyong Ho; Rhee, Ki-Hyeong (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Natural products including Agrimonia eupatoria are considered an incomparable source of molecular diversity that has led to the medicines, especially for pain treatment. To investigate the antinociception of Agrimonia eupatoria, we examined its activity in a rat model of cisplatin neuropathy. Materials and Methods: Male Sprague-Dawley rats received intraperitoneal (i.p.) cisplatin twice a week at a dose of 2 mg/kg (cumulative dose, 20 mg/kg) for 4 weeks. Before each injection, 2 ml of sterile saline solution was given subcutaneously to prevent renal damage via hyperhydration. The mice were treated with gabapetin as a positive control drug with a 100mg/kg intraperitoneal injection. A. eupatoria extract of 200mg/kg was solved in saline and then treated by oral administration. Results: The mice treated with A. eupatoria showed lower withdrawal duration in the pin-prick and plantar tests, and a higher withdrawal threshold in the paw-withdrawal threshold test as compared to control animals in a cisplatin-induced neuropathic model. In the case of cold-allodynia, A. eupatoria treatment increased paw-withdrawal duration in a chemical test. A. eupatoria showed a more outstanding effect than gabapentin in all used tests for preventing cisplatin-induced nerve injury for 4 weeks. Conclusions: Our results suggest that A. eupatoria extract showed an antinociceptive effect in the pin-prick test, plantar test, and paw-withdrawal threshold test using a cisplatin-induced neuropathic rat model.